Is economic recovery a myth? Robust estimation of impulse responses - Coen N. Teulings; Nick Zubanov (Center for Economic Studies and ifo Institute (CESifo), 2010)
There is a lively debate on the persistence of the current banking crisis' impact on GDP. Impulse Response Functions (IRF) estimated by Cerra and Saxena (2008) suggest that the effects of earlier crises were long-lasting. We show that standard estimates of IRFs are highly sensitive to misspecification of the underlying data generation process. Direct estimation of IRFs by a methodology similar to Jorda's (2005) local projection method is robust to misspecifications of the data generation process but yields biased estimates when country fixed effects are added. We propose a simple method to deal with this bias, which we apply to panel data from 99 countries for the period 1974-2001. Our estimates suggest that an average banking crisis leads to an output loss of around 10 percent with little sign of recovery. GDP losses from banking crises are more severe for African countries and economies in transition.
Keywords: G01; E27; C53; 330; banking crisis; impulse response; panel data; Bankenkrise; Wirtschaftliche Anpassung; Schätzung; Welt